2010
DOI: 10.1027/1866-5888/a000006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Demand-Control Model

Abstract: This study among 12,359 employees working in 148 organizations tested the interaction hypothesis of the Job Demands-Resources (JD-R) model. Accordingly, employees endorse most positive work attitudes (task enjoyment and organizational commitment) when job demands and job resources are both high. Results of moderated structural equation modeling analyses provided strong support for the hypothesis: 15 of the 16 hypothesized interactions were significant for task enjoyment and 13 of the 16 interactions were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
200
3
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 428 publications
(236 citation statements)
references
References 54 publications
(107 reference statements)
18
200
3
15
Order By: Relevance
“…Researchers have therefore frequently controlled for work characteristics when investigating recoveryrelated variables like psychological detachment (e.g., Fritz et al, 2010;Sonnentag, 2003). In order to be able to control for potential confounding effects, we therefore chose to control for workload and time pressure with a German translation of the Questionnaire on the Experience and Evaluation of Work (VBBA; van Veldhoven & Meijman, 1994; see also Bakker, Veldhoven, & Xanthooulou, 2010). The VBBA measures quantitative work demands in terms of workload and time pressure with 11 items.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have therefore frequently controlled for work characteristics when investigating recoveryrelated variables like psychological detachment (e.g., Fritz et al, 2010;Sonnentag, 2003). In order to be able to control for potential confounding effects, we therefore chose to control for workload and time pressure with a German translation of the Questionnaire on the Experience and Evaluation of Work (VBBA; van Veldhoven & Meijman, 1994; see also Bakker, Veldhoven, & Xanthooulou, 2010). The VBBA measures quantitative work demands in terms of workload and time pressure with 11 items.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, whereas job demands are generally the most important predictors of such outcomes as exhaustion, psychosomatic health complaints, and RSI (e.g., Hakanen et al, 2006), job resources are generally the most important predictors of work enjoyment, motivation, and engagement (Bakker, Hakanen et al, 2007;Bakker, Van Veldhoven et al, 2010). A number of studies have supported the dual pathways to employee well-being proposed by JD-R theory, and showed that it can predict important organizational outcomes.…”
Section: Two Processesmentioning
confidence: 86%
“…El modelo se ha utilizado para predecir el burnout [estar quemado en el trabajo] (Bakker, Demerouti y Euwema, 2005, 2008Demerouti et al, 2001), el compromiso organizacional (Bakker, Van Veldhoven y Xanthopoulou, 2010), la conexión con el trabajo (Lewig, Xanthopoulou, Bakker, Dollard y Metzer, 2007) y el engagement (Bakker, Hakanen, Demerouti y Xanthopoulou, 2007;Hakanen, Bakker y Schaufeli, 2006). Además, el modelo DRL se ha utilizado para predecir las consecuencias de estas experiencias, tales como el absentismo por enfermedad (p.…”
Section: La Teoría De Demandas Y Recursos Laboralesunclassified
See 2 more Smart Citations